2005
DOI: 10.1539/joh.47.218
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress in Nurses in Psychiatric Institutions in Taiwan

Abstract: with low job control, high psychological demand, and perceived occupational stress. A lower mental health score was associated with low job control, high psychological demand, low workplace support, and perceived occupational stress. We concluded that nurses in psychiatric institutions are under significant stress related to work factors. (J Occup Health 2005; 47: 218-225)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
93
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 27 publications
18
93
2
5
Order By: Relevance
“…The results obtained, however, differ from those obtained by other authors. Analyses conducted by Shen et al demonstrated that nurses who were widows or divorcees experienced much higher stress levels than married nurses [47]. Other studies indicate a link between the level of professional stress and having children [48].…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained, however, differ from those obtained by other authors. Analyses conducted by Shen et al demonstrated that nurses who were widows or divorcees experienced much higher stress levels than married nurses [47]. Other studies indicate a link between the level of professional stress and having children [48].…”
Section: Discussionmentioning
confidence: 99%
“…Because of a skewed distribution, the two domains were divided into quartiles using the lowest quartile to indicate poor health-related quality of life. A similar approach has been previously used by a study based on SF-12 14) . The magnitude of the statistical association between explanatory variables and poor quality of life was measured by the odds ratio and 95% confidence intervals, obtained by multiple logistic regression.…”
Section: Discussionmentioning
confidence: 99%
“…A low level of control and high psychological demand (job strain) were associated with a poor HRQL in the mental and physical domains in workers on a production line in Malaysia 13) . A poor general and mental health score was also associated with reduced control and high psychological demand, and with decreased social support at work among nurses at a psychiatric hospital in Taiwan 14) . Statistically significant associations between adverse psychosocial working conditions and poor quality of life were also found among cleaning workers in Las Vegas.…”
mentioning
confidence: 99%
“…They are faced with a series of special stressful factors such as infectious diseases, harmful chemicals and rays, disproportion between the numbers of patients and numbers of nurses, employment in non-fixed shifts, and dealing with the death of patients. In this regard, it is believed that many stressful factors in this profession will cause physical and psychological disorders (6).…”
Section: Introductionmentioning
confidence: 99%